Determinants of Employee Organizational Citizenship Behavior in Indonesia: Evidence from a Systematic Literature Review - Anna Triprasidhani Juniasri; Deti Mulyo Harsono; Sapta Dwikardana (Annals of Management and Organization Research, 2026)
Purpose: This study aimed to identify and synthesize key factors influencing Organizational Citizenship Behavior (OCB) by systematically reviewing prior empirical studies. Research Methodology: This study adopted a descriptive qualitative literature review approach. A total of 13 peer-reviewed journal articles focusing on Organizational Citizenship Behavior were selected based on predefined inclusion criteria. The selected studies were systematically identified, screened, mapped, and analyzed, and the findings were synthesized using a thematic analysis approach to identify the dominant determinants and research gaps related to OCB. Results: The review revealed that work–life balance, employee engagement, job satisfaction, leadership, and interpersonal communication are the most frequently identified factors influencing Organizational Citizenship Behavior. These factors affect OCB both directly and indirectly through mediating variables such as job satisfaction, burnout, and self-efficacy. The findings also indicate variations in the results across different industries and employee demographics. Conclusions: This study confirms that work–life balance is a critical determinant of enhancing voluntary employee behaviors that benefit organizational effectiveness. However, inconsistencies across studies suggest that contextual factors, including industry characteristics and workforce demographics, play an important role in moderating these relationships. Limitations: This review was limited by the number of studies analyzed and the diversity of the research contexts. Future research should incorporate cultural dimensions, generational differences, and flexible work arrangements to provide a more comprehensive understanding of Organizational Citizenship Behavior. Contributions: This study contributes to the literature by providing a contextual synthesis of the key determinants of Organizational Citizenship Behavior in Indonesia, offering insights for both scholars and practitioners in human resource management.